A Survey of Common Practices in Infancy Research: Description of Policies, Consistency Across and Within Labs, and Suggestions for Improvements. (16th March 2017) - Eason, Arianne E.; Hamlin, J. Kiley; Sommerville, Jessica A.
Abstract : Psychology is currently in a period of unprecedented self‐reflection, with particular attention being paid to research practices and policies. Although infancy researchers have a history of attending to research practice in the form of papers outlining how to best implement various methods and paradigms, less is known about the particular practices currently being used by researchers in the field, making it difficult to identify areas for improvement. To address this issue, we developed an online survey for measuring methodological practices in infancy laboratories around the world. Our results suggest that infancy researchers adopt a range of a priori research practices. Individuals earlier in their training (particularly within the first year) were more likely to report not knowing their lab's policies, especially regarding issues that arise late in the research process. Members of the same lab agreed on lab policies at above‐chance levels; however, improvements could be made. The use of clearly problematic research practices was relatively rare; however, several "risk‐permeable" practices were identified that may, under select circumstances, threaten data integrity. We discuss how our results could be used to improve practice in infant research.